(untitled) (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2022)
Cloud computing is most rising field of the field of computing. Be that as it may, choosing the correct cloud specialist organization to trust with your foundation, basic applications and delicate information can be a troublesome procedure. In this Research paper different cloud benefits alongside the related cloud security issues has been talked about and dissected and a correlation of three significant cloud specialist organizations in particular Amazon AWS, Windows Azure and Google App Engine have been done as far as the administration and security issues. It will help the purchasers of cloud administrations to pick the correct cloud supplier as indicated by their prerequisites and necessities.